2016
DOI: 10.22319/rmcp.v7i3.4212
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de taninos sobre características físicas y sensoriales de carne de bovinos en engorda

Abstract: Para evaluar la adición de 0.3 % extracto de taninos en las características físicas y sensoriales de la carne de bovinos engordados de forma intensiva, se utilizaron muestras del músculo Longissimus dorsi de 16 toretes (Bos taurus x Bos indicus), los cuales durante los últimos 70 días de la engorda recibieron dieta de finalización (13.3% PC y 2.0 Mcal ENm/kg de MS), y en grupos de ocho se asignaron al azar para recibir uno de dos tratamientos: 1) dieta de finalización (testigo); 2) testigo más 0.3% (base seca)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Some studies have shown that the inclusion of natural sources of polyphenols such as CTs in the diet of small ruminants improves productive variables, preserves the quality of the meat, prolongs shelf life, and prevents deterioration (Dawson et al, 2011;Elmer et al, 2017;Mkhize et al, 2018). The results have been variable, depending on the source of tannins and the dose used in the ration (McNabb et al, 1993;Luciano et al, 2009Luciano et al, , 2011Liu et al, 2016;Guerra-Rivas et al, 2016;Ortiz-López et al, 2016;Lobón et al, 2017;Kamel et al, 2018;Guerreiro et al, 2020). Therefore, the objective of this study was to determine the fattening performance and characteristics of the lambs supplemented with CTs from the extract of Acacia mearnsii (EAM).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the inclusion of natural sources of polyphenols such as CTs in the diet of small ruminants improves productive variables, preserves the quality of the meat, prolongs shelf life, and prevents deterioration (Dawson et al, 2011;Elmer et al, 2017;Mkhize et al, 2018). The results have been variable, depending on the source of tannins and the dose used in the ration (McNabb et al, 1993;Luciano et al, 2009Luciano et al, , 2011Liu et al, 2016;Guerra-Rivas et al, 2016;Ortiz-López et al, 2016;Lobón et al, 2017;Kamel et al, 2018;Guerreiro et al, 2020). Therefore, the objective of this study was to determine the fattening performance and characteristics of the lambs supplemented with CTs from the extract of Acacia mearnsii (EAM).…”
Section: Introductionmentioning
confidence: 99%